Comparison of interleukin-6 and serum creatinine levels in preeclampsia and normal pregnancy patients: A cross-sectional study in Indonesia - Dewi, Syerli R.; Yeni, Cut M.; Munizar, Munizar; Dewi, Tgk. Puspa; Utami, Niken A.; Rusnaidi, Rusnaidi (Narra Sains Indonesia, 2026)
Preeclampsia (PE) is a complication of pregnancy with high morbidity and mortality, characterized by endothelial dysfunction, systemic inflammation, and impaired renal function. Interleukin-6 (IL-6) and serum creatinine have potential as biomarkers for early detection of PE; however, data from Indonesia are limited. The aim of this study was to compare IL-6 and serum creatinine levels between pregnant women with PE and normotensive controls, as well as their diagnostic performance in identifying PE. A cross-sectional study involving pregnant women with PE and normotensive controls was conducted at Dr. Zainoel Abidin Hospital, Banda Aceh, Indonesia. Serum IL-6 and creatinine levels were measured using the ECLIA method. Levels were compared using the Mann–Whitney test; diagnostic performance was assessed using receiver operating characteristic (ROC) curve analysis, and multivariable logistic regression was used to evaluate combined diagnostic contribution. A total of 68 pregnant women were included, comprising 34 patients with PE and 34 normotensive controls. Median IL-6 levels were significantly higher in the PE group (16.05 pg/mL) than in the control group (3.71 pg/mL). Receiver operating characteristic analysis demonstrated excellent diagnostic performance of IL-6, with an are under the curve (AUC) of 0.831 (95%CI: 0.734–0.929). At an optimal cutoff value of 5.52 pg/mL, IL-6 achieved a sensitivity of 73.53%, specificity of 76.47%, and diagnostic accuracy of 86.76%. Median serum creatinine levels were also significantly elevated in the PE group (0.56 mg/dL) compared with controls (0.44 mg/dL; p<0.001). The AUC for serum creatinine was 0.806 (95%CI: 0.700–0.912), indicating good diagnostic performance. At a cutoff value of 0.475 mg/dL, serum creatinine demonstrated a sensitivity of 70.59%, specificity of 73.53%, and accuracy of 72.06%. Multivariable logistic regression confirmed that IL-6 (B=0.123; p=0.005) and serum creatinine (B=9.306; p=0.023) were independently associated with PE, explaining 57.5% of PE variability (Nagelkerke R²=0.575). These findings indicate that serum IL-6 and creatinine are significantly associated with PE, and their combined assessment shows potential as a predictive biomarker with good diagnostic performance.